Factors Affecting Whistleblowing Intention : A Study of Accounting Undergraduate Students - Ambar Kusumaningsih (AKRUAL: JURNAL AKUNTANSI, 2021)
Whistleblowing has gained more attention worldwide. As many as 43% of fraudulent acts can be detected thanks to tips or whistleblowing. Graduates from the Accounting major are future auditors and accountants who are most likely to face illegal actions in their careers. This study aims to understand the factors that motivate undergraduate accounting students’ whistleblowing intention. This study explores how the factors of Consequence’s Magnitude (CM), Social Agreement (SA), Proximity (PX) and Fear of Retaliation (FR) can affect Whistleblowing Intention (WI). The results of this study indicate that the CM, SA, and PX factors have no significant effect on WI, while the FR factor has a significant effect on WI. This research is expected to positively contribute to assisting Lecturers of the Accounting Department in designing a curriculum to encourage undergraduate Accounting students to have stronger WI and be ready to be practised in the actual working environment. This research is also useful for future researcher who would like to explore the topic of whistleblowing intention.